Oral health evaluation and dental treatment given for head and neck onco-patient before starting radiotherapy - Lomtu Ronrang; Neizekhotuo Brian Shunyu; Alice Lyngdoh (Oral Oncology Reports)
This is the study on oral health evaluation and dental treatment given to seventy-five head and neck cancer patients before the starting of radiotherapy. Mouth Scaling was done in all the patients, thirty-nine patients underwent tooth extraction, thirty-nine were requiring filling with Glass Ionomer Cements (GIC) materials, root canal treatment was given in fourteen patients and topical fluoride application was done in three patients. Proper oral hygiene instructions were given to all the patients.